2008
DOI: 10.1556/avet.56.2008.3.12
|View full text |Cite
|
Sign up to set email alerts
|

Synchronisation of lambing with low doses of dexamethasone in Chios ewes — Short communication

Abstract: The purpose of the present study was to investigate the feasibility of improving the synchronisation of lambing after oestrus synchronisation and artificial insemination (AI). To this end, low doses of dexamethasone 21-isonicotinate (DEX) alone or in combination with prostaglandin F 2a (PG) were used in five treated groups (n = 20 each) and one control group (n = 136) of Chios ewes. On day 143 of pregnancy 1.5 mg DEX was given in Group 5, while on day 146 the following treatments were applied: 0.0375 mg PG in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 4 publications
1
6
1
Order By: Relevance
“…The wide variation in time elapsed between induction of parturition and lambing (0.5-177 h) led us to conclude that this dexamethasone regimen was impractical for parturition synchronization of a flock of sheep. The interval from dexamethasone treatment to parturition appeared to be greater and more variable compared to that reported by Tsiligianni et al (2008) (13.0-98.3 h), who used low doses of dexamethasone (1.5-2.0 mg per ewe) to synchronize lambing in Chios ewes.…”
Section: Discussioncontrasting
confidence: 52%
“…The wide variation in time elapsed between induction of parturition and lambing (0.5-177 h) led us to conclude that this dexamethasone regimen was impractical for parturition synchronization of a flock of sheep. The interval from dexamethasone treatment to parturition appeared to be greater and more variable compared to that reported by Tsiligianni et al (2008) (13.0-98.3 h), who used low doses of dexamethasone (1.5-2.0 mg per ewe) to synchronize lambing in Chios ewes.…”
Section: Discussioncontrasting
confidence: 52%
“…Fylling (1971) could not induce parturition in sheep using a dose of 4 mg DEXA on day 133 of gestation. However, Tsiligianni et al (2008) were able to induce the birth process with as little as 1.5 mg of DEXA on day 146 of gestation. The authors explain this observation with the fact that this low dose was given very close to the normal due date (Tsiligianni et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, Tsiligianni et al (2008) were able to induce the birth process with as little as 1.5 mg of DEXA on day 146 of gestation. The authors explain this observation with the fact that this low dose was given very close to the normal due date (Tsiligianni et al, 2008). The inducing dose of 16 mg per ewe was chosen according to the recommendations by Penning and Gibb (1977) and by Ingoldby and Jackson (2001).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the present study also evaluated in G2 whether the administration of half the conventional dose (8mg) would have the potential to induce labor with the same efficiency. Tsiligianni et al (2008) were able to induce the birth process with just two mg and one and a half mg of dexamethasone at 146 days of gestation, which suggests that induction of labor in ewes with advanced gestation, close to the date of physiological birth, may be performed with low doses. However, the same authors observed dystocia in some births, which made it necessary to use obstetric maneuvers.…”
Section: Resultsmentioning
confidence: 96%
“…There was also the occurrence of stillbirths and placental retention in a 10% average among induced groups, which justified the use of dexamethasone. In the present study, it was used a higher dose than that reported by Tsiligianni et al (2008) in an attempt to avoid occurrences of the problems above.…”
Section: Resultsmentioning
confidence: 99%